Intramedullary Nailing of Femoral Diaphyseal Metastases: Is it Necessary to Protect the Femoral Neck?. Issue 4 (April 2015) - Moon, Bryan; Lin, Patrick; Satcher, Robert; Bird, Justin; Lewis, Valerae
Abstract: Background: Intramedullary nailing is the accepted form of treatment for impending or pathologic fractures of the femoral diaphysis. Traditional teaching promotes the use of a cephalomedullary nail so that stabilization is provided for the femoral neck in the event that a future femoral neck metastasis develops. However, that approach may add cost, surgical time, blood loss, and added radiation exposure to staff members, and there is limited evidence in the literature that supports this practice. Questions/purposes: The purpose of our study was to evaluate the incidence of femoral neck metastases in patients who underwent femoral nailing of diaphyseal metastases. Patients and Methods: Retrospective analysis of our Musculoskeletal Oncology database identified 145 femoral nailings performed for metastatic disease, myeloma, or lymphoma of the femoral diaphysis between 2001 and 2011. Average patient age was 59 years. One hundred forty‐one patients underwent 145 femoral nailings (four were bilateral). One hundred forty‐four of the nails used were cephalomedullary implants and one was a flexible nail. Thirty‐six (25%) femurs had sustained a pathologic fracture and 109 (75%) femurs were treated as impending fractures. Eighty‐four patients received either preoperative or postoperative radiation therapy. Average radiographic followup was 13 months and average postoperative survival was 16 months. Of the 141 patients in this series, 121 (86%) are known to have died at a median of 9 months (range, 0.1‐133 months) after surgery. The latest followup radiographs were obtained at a median of 5 months after the femoral nailing (range, 0‐119 months). Of the 90 patients with documented dates of death and radiographic followup greater than zero months, 76 (84%) had radiographs available within a year of death. Thirty‐one patients had zero months radiographic followup. The median survival for this group of patients was only 0.9 months (range, 0.1‐12 months). Results: No patients (0%) in this series had femoral neck metastases develop postoperatively. Conclusion: Despite traditional teaching that supports the use of cephalomedullary implants when treating metastatic disease of the femur, we were unable to identify a single patient who had femoral neck metastasis after surgery on the femur. Our findings do not support the use of cephalomedullary implants in this patient population for the sole purpose of prophylactic femoral neck stabilization; however, this series was relatively small, and the experiences of other centers will be needed to come to a more‐complete sense of the frequency of what in all likelihood is a rare event. Level of Evidence: Level IV, therapeutic study.